Schools as learning organizations - Nsibande, Njabuliso H. (My University, 2006)
Since the 1990s, the corporate concept of learning organizations has been promoted as a solution to problems caused by ever-changing educational reforms and as a model for schools in the twenty-first century. Through an indepth analysis of two South African secondary schools in Gauteng, this study examines how organizational learning is nurtured and sustained, and considers whether and how the concept of learning organizations is applicable in schools. Three perspectives on learning organizations are considered: the normative, developmental and capability perspectives. The investigative framework links theories on organizational memory, organizational learning, organizational change and complexity theory to provide insights into why some organizations are ‘smarter’ than others and why educational reforms and innovations often fail. The study used a multi-method approach, within a nested case design, at two contrasting schools, each facing the challenges of a changing society and education system, but under very different conditions: a state school in a poor informal settlement and a wealthy faith-based, independent school. Research participants included two principals, four heads of departments, ten teachers and fourteen learners. Although learners were included, the study focuses primarily on teachers and school leaders. At each school, key informants were selected from among those acknowledged to have contributed significantly to the school, either individually or as team members. In-depth interviews, as well as teachers’ narrative accounts of their own learning and unlearning, and a variety of schoolgenerated documents provided the data set. Two approaches were used for the stories of learning and unlearning – personal writing and elicitation through narrative interviews. Findings pertain to participating schools, but also provide a basis for more general claims. In ethos, practices and leadership, both schools reflect a deep commitment to improving learners’ lives. However, schools cannot operate as learning organizations unless they can harness individual staff members’ aspirations as well. Internal and external circumstances impeded organizational learning and reciprocal professional commitment among staff. These included: personal problems; an individualistic school learning system with limited social interaction; concomitant anxiety about collaborative professional learning; a value system that favours competition; routine rather than reflective contexts for professional learning and communication; and unacknowledged gender issues. Another feature of a learning organization is a reflective openness to change. Yet both schools strive for stability and conformity to rules, and neither has developed tools for recognizing turning points, disjunctures and triggers for change. Learning organizations emphasize collective learning; yet teachers and department heads are ‘starving’ for personal recognition, especially in cases where they have become multi-skilled in the course of career advancement. The study also analyses complexities of school leadership and resulting trade-offs that have to be made between satisfying the diverse needs of school members and responding to external demands, especially at the level of policy. Overall, the vi study demonstrates that while the related concepts of learning organizations and organizational learning are generative for understanding, structuring and leading schools, the definitive purposes of schools and the external pressures one them preclude a simple transfer from the corporate world.
Faculty of Humanities School of Education PHD 9605681F njabulison@mstp.org.za
Keywords: Learning; Organisation; schools; educational change; complexity; theory; leadership